ppt 5 - GetMoreMath

Report
How do you distribute?
(
)
(2X
)
(2X + 300)
(2X + 300)+ (2X + 300)
(2X + 300)+ (2X + 300) + (2X + 300)
(2X + 300)+ (2X + 300) + (2X + 300)
(2X + 300)
(2X + 300)+ (2X + 300) + (2X + 300)
3(2X + 300)
3(2X + 300)
3(2X + 300) =
3(2X + 300) =
3(2X + 300) = 3(2X)
3(2X + 300) = 3(2X)
3(2X + 300) = 3(2X) + 3(300)
3(2X + 300) = 3(2X) + 3(300)
3(2X + 300) = 3(2X) + 3(300)
6X
3(2X + 300) = 3(2X) + 3(300)
6X + 900
How do you distribute?
-4(3 – 5X)
-4(3 + -5X)
-4(3 + -5X) =
-4(3 + -5X) =
-4(3 + -5X) = -4(3)
-4(3 + -5X) = -4(3)
-4(3 + -5X) = -4(3) +
-4(3 + -5X) = -4(3) + -4(-5X)
-4(3 + -5X) = -4(3) + -4(-5X)
-4(3 + -5X) = -4(3) + -4(-5X)
-12
-4(3 + -5X) = -4(3) + -4(-5X)
-12 + 20X
X(-2X – 7)
X(-2X + -7)
X(-2X + -7) =
X(-2X + -7) =
X(-2X + -7) = X(-2X)
X(-2X + -7) = X(-2X) +
X(-2X + -7) = X(-2X) + X(-7)
X(-2X + -7) = X(-2X) + X(-7)
X(-2X + -7) = X(-2X) + X(-7)
-2*X*X
X(-2X + -7) = X(-2X) + X(-7)
-2*X*X
2
-2X
X(-2X + -7) = X(-2X) + X(-7)
2
-2X
X(-2X + -7) = X(-2X) + X(-7)
2
-2X
+ -7X
-4X(-X + 6)
-4X(-1X + 6)
-4X(-1X + 6) =
-4X(-1X + 6) =
-4X(-1X + 6) = -4X(-1X)
-4X(-1X + 6) = -4X(-1X)
-4X(-1X + 6) = -4X(-1X) + -4X(6)
-4X(-1X + 6) = -4X(-1X) + -4X(6)
-4X(-1X + 6) = -4X(-1X) + -4X(6)
-4*-1*X*X
-4X(-1X + 6) = -4X(-1X) + -4X(6)
-4*-1*X*X
2
4X
-4X(-1X + 6) = -4X(-1X) + -4X(6)
2
4X
-4X(-1X + 6) = -4X(-1X) + -4X(6)
2
4X
– 24X
3 + 2(-X + 6)
3 + 2(-X + 6)
Add
Multiply
3 + 2(-X + 6)
3 + 2(-X + 6)
3+
3 + 2(-X + 6)
3+
3 + 2(-X + 6)
3 + -2X
3 + 2(-X + 6)
3 + -2X
3 + 2(-X + 6)
3 + -2X + 12
3 + 2(-X + 6)
3 + -2X + 12
3 + 2(-X + 6)
3 + -2X + 12
15 + -2X
-X(-X + 6) – 5X(-3)
-X(-X + 6) + -5X(-3)
-X(-X + 6) + -5X(-3)
-X(-X + 6) + -5X(-3)
-X(-X + 6) + -5X(-3)
-X(-X + 6) + -5X(-3)
-1*-1*X*X
-X(-X + 6) + -5X(-3)
-1*-1*X*X
X2
-X(-X + 6) + -5X(-3)
X2
-X(-X + 6) + -5X(-3)
X2 + -6X
-X(-X + 6) + -5X(-3)
X2 + -6X +
-X(-X + 6) + -5X(-3)
X2 + -6X +
-X(-X + 6) + -5X(-3)
-3*-5*X
X2 + -6X +
-X(-X + 6) + -5X(-3)
-3*-5*X
X2 + -6X + 15X
-X(-X + 6) + -5X(-3)
X2 + -6X + 15X
-X(-X + 6) + -5X(-3)
X2 + -6X + 15X
X2 + 9X
-X(-X + 6) + -5X(-3)
X2 + -6X + 15X
X2 + 9X
-17Y – 7(-10 – 10Y)
-17Y + -7(-10 + -10Y)
-17Y + -7(-10 + -10Y)
-17Y + -7(-10 + -10Y)
-17Y + -7(-10 + -10Y)
-17Y +
-17Y + -7(-10 + -10Y)
-17Y +
-17Y + -7(-10 + -10Y)
-17Y + 70
-17Y + -7(-10 + -10Y)
-17Y + 70
-17Y + -7(-10 + -10Y)
-17Y + 70 + 70Y
-17Y + -7(-10 + -10Y)
-17Y + 70 + 70Y
53Y + 70

similar documents